Emergency Continuous Peritoneal Dialysis using Flexible Tenckhoff Catheter inserted with Reinforced Purse String Suture : An efficient substitute of renal replacement therapy in Critically Ill Patients with AKI when Intermittent Hemodialysis, Sustained lo - Iqbal, Sarwar; Chowdhury, Tufayel Ahmed; Faruq, Mohammad Omar; Bhuiyan, ASM Manzur Morshed; Ananna, Mehruba Alam; Rahim, Muhammad Abdur; Samad, Tabassum; Haque, Wasim Md Mohosinul; Ahsan, ASM Areef; Ahmed, Fatema; et al. (Bangladesh Critical Care Journal, 2016)
Introduction : Renal replacement therapy (RRT) is often used to treat critically ill patients associated with acute or chronic renal failure. Peritoneal dialysis (PD) is an option when intermittent hemodialysis (IHD), sustained low efficiency dialysis (SLED) or Continuous renal replacement therapy (CRRT) are not feasible. PD customarily uses rigid catheter and cannot be used for more than 3 days as there is increased chance of infection and it can cause perforation of hollow viscera and often there is hemorrhage due to trauma to the adjacent organs. In this study we used Tenckhoff flexible PD catheter with double cuff and reinforced purse string suture1, So it can be used on an emergency basis and for indefinite period with minimal chances of complications commonly associated with rigid PD catheter. In this observational study emergency CPD using the procedure mentioned above in a compromised group of renal insufficiency patients was explored. Objectives : To determine if emergency RRT can be achieved by CPD using flexible Tenckhoff catheter placed with special reinforced sutures when IHD, SLED or CRRT is not feasible in critically ill patients. Material and Methods : Patients who failed to tolerate IHD, SLED or CRRT because of resulting hemodynamic instability and those who required dialysis urgently and for a prolonged period in Intensive Care Unit (ICU) were selected. There were 58 study cases who received emergency CPD after fulfilling inclusion criteria using flexible Tenckhoff catheter placed with special reinforced suture. These patients were on various life-support modalities having multiple co-morbidities. Regular exchanges were started manually with small volume on the day or the next day of catheter implantation, initially with 0.5-1 liter/session and subsequently with 2 liters per session after 15 days. Serum creatinine of study subjects were followed for 45 days and study subjects were followed for up to a year to check for survivability. Results : In 58 critically ill cases that fulfilled the criteria were included in the study. Average age was 67.05±14.43 years and 66% were male. Majority were diabetic 48 (82.75%) and the cause of AKI were sepsis in 39 cases (67.2%) acute cardiovascular insufficiency in 9 cases (AMI & NSTEMI 15.5%), gastroenteritis in 3 cases (5.2%), stroke in 4 cases (6.9%) and multi organ failure in 7 cases (12.1%). Average creatinine at the initiation of dialysis was 7.68 ± 3.15 and after 5 days it was 5.86± 2.8, after 10 days 4.08 ± 2.61, after 15 days 2.87 ± 2.1, one month 2.32± 1.90 and after one and a half months 2.31± 1.88. Volume overload was the indication of CPD in 22 (37.93%) patients but main indication was uremia in 36 (62.06%) cases. In ICU 23 (39.7%) patients expired within a short (within 7 days) period. In the remaining 30(42.9%) survived beyond 4 weeks (51.7); 22 (37.9%) beyond 12 weeks; 14(24.1%) beyond 24 weeks and 5(8.6)% beyond 1 year. In 4 (2.32%) patients PD catheter was removed as renal function improved. 35 patients were on mechanical ventilator and out of them 18 patients were weaned of mechanical ventilator (MV). 26 MV patents (including weaned off) survived beyond 4 weeks. Mechanical complications from PD catheter in situ were very low and there was catheter related infection only in two cases. Conclusion : Emergency CPD can be an alternate mode of renal replacement therapy (RRT) in critically ill patients where emergency IHD, SLED or CRRT are not feasible. It was accompanied with low risk of procedure related complications and well tolerated. Bangladesh Crit Care J March 2016; 4 (1): 3-8